Behind closed doors secrets of great management - Rothman, Johanna (Raleigh Pragmatic Bookshelf, 2005)
Great management is difficult to see as it occurs. It's possible to see the results of great management, but it's not easy to see how managers achieve those results. Great management happens in one-on-one meetings and with other managers---all in private. It's hard to learn management by example when you can't see it.
Includes bibliographic references (p. [159]-163) and index.
Keywords: Management--Handbooks